Thermodynamics of interaction of inulin complex with water - Yu. A. Maksimenko; O. I. Konnova; I. Yu. Aleksanian (Новые технологии, 2024)
Currently, the key trends in the global food market include the rapidly developing functional nutrition industry, which is of great interest to consumers. Inulin is a natural polysaccharide of plant origin, consisting of residues of E-fructofuranose (fructose). The object of the research is inulin extract from Jerusalem artichoke at different humidity levels. It has been established that to intensify the drying process of inulin extract, it is advisable to increase the mass transfer surface, which can be achieved by spraying the initial product, and using volumetric energy supply methods, in particular, radiation energy supply. The important and most energy-intensive stages of drying are carried out in the hygroscopic area of equilibrium humidity of the object of the research, which determines the intensity and mechanism of the dehumidification operation in order to increase the degree of perfection, select rational operating parameters, adapt to the object of the analysis and solve a mathematical model of removal moisture from it. Based on the sorption isotherms and hygroscopic parameters of the inulin extract obtained in preliminary studies, obtained by dehydrating the inulin extract from Jerusalem artichoke (variety «Skorospelka», grown by JSC «Chaganskoe», the bAstrakhan region), a thermodynamic analysis of the process of sorption and desorption was carried out in different ranges of humidity variation. The total binding energy of moisture with the dry residue of inulin and its thermodynamic components were found. The data obtained do not contradict known literature sources and can be recommended when designing processes for removing moisture from inulin extract and designing drying devices.